analisis faktor produksi padi di jawa timur tahun 2005-2015 dengan metode cobb douglass - pitaloka, sekar dyah (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
The purpose of this study was to find out how and how much influence the independent variable (rice field area and harvested area) had on the dependent variable (rice production) in East Java in 2005-2015. This type of research is quantitative research, the data used are in the form of numbers and also the data analysis used is statistical and econometric methods. The data analysis technique used is the Cobb Douglass approach with multiple linear analysis. Based on the results of the analysis of the data and also the discussion, the results obtained if the rice production factors that have a positive and significant effect are the area of ​​rice fields and also the area of ​​harvest. The diversity of rice farming production in East Java is explained by an independent variable of 94% while the remaining 6% is explained by other variables not included in the equation. Other variables that have an influence on rice production in East Java include labor variables, seeds used, use of fertilizers, age of farmers and also the education taken by farmers in East Java.